1979
DOI: 10.1111/j.1432-1033.1979.tb12925.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Biochemical Solid‐Phase Techniques in the Study of Alcohol Dehydrogenase

Abstract: The EE and SS isozymes of horse liver alcohol dehydrogenase have been immobilized separately to weakly CNBr-activated Sepharose 4B. The resulting immobilized dimeric preparations lost practically all of their activity after treatment with 6 M urea. However, enzyme activity was regenerated by allowing the urea-treated Sepharose-bound alcohol dehydrogenase to interact specifically with either soluble subunits of dissociated horse liver alcohol dehydrogenase or soluble dimeric enzyme. The regeneration of steroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The success of interspecies hybridization of horse liver ADH with human (3^^isozyme suggested structural homology between the horse and the human enzyme (Schenker et al, 1971;Berger et al, 1974) even before the amino acid sequence of the human enzyme was reported. Moreover, by carrying out the dissociation/ reassociation on enzyme attached to a solid support, it was also demonstrated that the monomer of horse liver ADH is inactive (Andersson & Mosbach, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The success of interspecies hybridization of horse liver ADH with human (3^^isozyme suggested structural homology between the horse and the human enzyme (Schenker et al, 1971;Berger et al, 1974) even before the amino acid sequence of the human enzyme was reported. Moreover, by carrying out the dissociation/ reassociation on enzyme attached to a solid support, it was also demonstrated that the monomer of horse liver ADH is inactive (Andersson & Mosbach, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Some theoretical problems associated with structure and function of alcohol dehydrogenases also have been solved by studying suitably immobilized enzymes. 8 The present work has been aimed at immobilization of horse liver alcohol dehydrogenase (EC 1.1.1.1) (LADH) to glycidyl methacrylate with ethylene dimethacrylate copolymers, and a choice of the most suitable type of the carrier Biotechnology and Bioengineering, Vol. XXIV, Pp.…”
Section: Introductionmentioning
confidence: 99%